2022
DOI: 10.1016/j.jretconser.2021.102867
|View full text |Cite
|
Sign up to set email alerts
|

Online shopping adoption during COVID-19 and social isolation: Extending the UTAUT model with herd behavior

Abstract: The COVID-19 pandemic has created a new reality for consumers all around the globe. To cope, users of digital technologies have faced the necessity of adopting and using specific technologies practically overnight. They are doing this under the condition of social isolation, all while facing the fear of catching the disease. The purpose of the paper is to study the way unexpected circumstances cause disruptions in existing theoretical models and their implications for the post-COVID-19 era. Therefore, the pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 81 publications
3
76
0
5
Order By: Relevance
“…During the COVID-19 period, people have become much more dependent on technology and information systems ( Erjavec and Manfreda, 2022 ). Technology is being used more and more because it can keep people apart and make them safer ( Eger et al, 2021 ).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 period, people have become much more dependent on technology and information systems ( Erjavec and Manfreda, 2022 ). Technology is being used more and more because it can keep people apart and make them safer ( Eger et al, 2021 ).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…During unusual events, like the pandemic, older people quickly move to broader sources of information, like broadcast media ( Akar, 2021 ). Also, because older adults' face-to-face communication was suddenly cut off, they started to rely mostly on social media apps as their only source of news ( Erjavec and Manfreda, 2022 ). Alhaimer (2022) indicated that stronger messages in the media may cause more fear, which may lead to more compliance with social-distance and lockdown policies.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in the UTAUT model, performance expectation refers to the extent to which users believe that technology can help them improve their work performance (Erjavec and Manfreda, 2021 ). It is the main factor affecting users' online learning.…”
Section: Online Chinese Learning (Ocl)-oriented Learning Satisfaction...mentioning
confidence: 99%
“…To investigate the adoption of autonomous decision-making processes and contribute to the state-of-the-art knowledge in the field, this study adopts the unified theory of acceptance and use of technology (UTAUT) model. The use of the UTAUT model is appropriate because this theory has been applied to investigate technology adoption in retailing [20]. Additionally, this study adds attitude to the UTAUT theory.…”
Section: Introductionmentioning
confidence: 99%